Methodological guidelines for coursework in the discipline «Water supply, sanitation and water quality improvementt» - Dushkin, Stanislav Sergeyevich (Харківський національний автомобільно-дорожній університет, 2025)
The methods for calculating water volumes to meet the needs of the city and firefighting, municipal needs and the needs of industrial enterprises are presented. The methodological guidelines can also be used during diploma design
Keywords: water supply; sanitation; water quality improvement; 628.16